THE SYNTHESIS OF LOCAL AND FOREIGN STYLES IN UZBEK ARCHITECTURE: THE APPLICATION OF EASTERN AND WESTERN ELEMENTS - A. R. Abobakirov (Modern American Journals, 2025)
Uzbek architecture represents one of the most sophisticated cultural syntheses in world history, where local traditions of Central Asia harmonized with external influences from both the East and the West to create a unique architectural language. Over the centuries, Uzbekistan’s monumental ensembles, religious complexes, civic structures, and modern constructions have absorbed and transformed elements from Persian, Arab, Turkic, Mongol, Russian, and European traditions. This study explores the ways in which local and foreign styles have interacted, emphasizing the continuous dialogue between Eastern ornamental, symbolic, and spiritual aesthetics and Western structural, material, and technological innovations. Using a methodological framework that combines historical-architectural analysis, heritage studies, and comparative stylistics, the research examines the synthesis of forms during the Timurid era, the Khanate periods, the Russian imperial and Soviet epochs, and the post-independence renaissance of national architecture. Results demonstrate that Uzbek architecture has historically preserved its indigenous identity while selectively incorporating external features, producing hybrid styles that reflect both resilience and adaptability. The discussion situates these developments within broader global processes, highlighting the significance of Uzbek architecture in shaping cross-cultural understanding and architectural diplomacy. The conclusion stresses that the integration of Eastern and Western elements in Uzbekistan is not merely a matter of stylistic borrowing, but a creative process that continues to enrich both national identity and global architectural heritage.
Keywords: Uzbek Architecture; Eastern and Western Elements; Cultural Synthesis; Timurid Architecture; Russian Imperial Influence; Soviet Modernism; Architectural Heritage